Spory kompetencyjne i spory o właściwość w zakresie ochrony środowiska w świetle orzecznictwa Naczelnego Sądu Administracyjnego - Stelmasiak, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article presents the key problems encountered in resolving competence disputes and jurisdictional disputes by the Supreme Administrative Court in matters of environmental protection. The analysis of the case law of the Supreme Administrative Court showed that most of this type of jurisdictional disputes, that is between local government units, and conflicts of competence between organs of these entities and government administration agencies, concerns water law, the law on waste and determining the right authority to issue an administrative decision on environmental conditions of realization of a project. It should also be noted that such disputes may be positive or (more often) negative, when no authority considers that it has jurisdiction to settle a particular administrative case.
Keywords: legal protection of the environment; competence dispute; jurisdictional dispute; Supreme Administrative Court